PENGUNGKAPAN BLUE ACCOUNTING DAN KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH PROVINSI MALUKU - Ardiansyah Ardiansyah; Barus Umarella (AKUNTANSI DEWANTARA, 2022)
The research objectives are: (1) to determine the disclosure of the application of the blue accounting concept; (2) to find out the contribution of blue accounting to the PAD of Maluku Province which comes from the Tourism, Fisheries, and Marine Sector. This type of research is descriptive qualitative. Documentation and observation data collection techniques. The sources of data in this study are: (1) Maluku Provincial Tourism Office; (2) Maritime Affairs and Fisheries Service of Maluku Province; (3) Regional Revenue Agency of Maluku Province; and (4) the Central Bureau of Statistics of Maluku Province. Observations in this study were conducted in the district government area. Central Maluku and Ambon City, Maluku Province. This research was conducted from June to October 2022. Findings: (a) Blue accounting is a derivative of blue economics covering land and sea-based economic development such as the development and maintenance of the coastal tourism sector, coastal area development, community commodities, technological innovation, human resources, supervision natural resources, and fisheries sector in a sustainable manner; (b) In the last 5 years the tourism sector has been able to contribute to the Maluku Province's Original Regional Revenue. Future research is expected to be able to comprehensively examine blue accounting practices in the tourism sector in Maluku Province through concrete steps and describe the contribution of the community-managed tourism sector to Maluku Province PAD. The practical contribution of this research is addressed to the Prov. Maluku through the Department of Tourism and the Department of Marine Affairs and Fisheries to give serious and intensive attention.